On invariant tori of countable systems of differential equations with delay - Elnazarov, A. A.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We obtain conditions for the existence and smoothness of invariant tori of countable systems of differential equations with delay.